Subsequent Complications Following COVID-19 an Systematic Reviews - Majed Saud B Alotaibi,; Ghadeer Abdullah Abdullah Mutabi,; Areej Saddiq Mohammed Hindi,; Areej Ali Yahya Safhi,; Ali Hameed Mohammed Alabsi,; Hassan Zaid Mohammed Alzaid,; Saeed Hamzah Matar Alharbi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: From COVID-19, a broad spectrum of early, intermediate and late complexities have been recognized with this SARS-CoV-2 since then. Still, there can be sequelae that persist from recovery following the acute illness of COVID-19. Research aim is to thoroughly examine the current evidence on delayed consequences given to COVID-19. Methods: A broad search was performed in various electronic databases including Scopus, Web of Science, PubMed, Embase (up to Oct 2024) using specific keywords for an exhaustive review. Results: A systematic review on the most common complications underlying COVID-19 Long COVID in 30 selected studies revealed a diverse set of major complications of developing long COVID-19. Neurologic and psychiatric presentations dominated the list of the sequelae that followed next were respiratory, musculoskeletal, rheumatologic considerations and ciring cardiovascular as well hepatic and gastrointestinal aspects. Conclusion :Concluding, the lingering consequences of COVID-19 influence multiple physiological systems ranging from mild to severe and cases with these latter extremes. Long COVID-19 patients with my journey fatigue, and a swath of neuropsychiatric morbidities, therefore fatigue has been among the most consistently described late complications seen in individuals affected by prolonged COVID. Next are the respiratory problems that include dyspnea, cough and chest tightness representing important long coronavirus disease 2019. Due to the enduring and delayed nature of these sequelae, there should be ongoing vigilance for the demonstration of characteristic signs and symptoms in both patients who are well as those who have deteriorated.